ANALISA PEMASARAN PRODUK JURUSAN TEKNIK SIPIL (JTS) TERHADAP KEPUTUSAN PENGGUNA JASA MEMILIH JURUSAN TEKNIK SIPIL - Penina T Istia (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2021)
Abstract:Marketing Analysis of JTS Products on Service User Decisions to Select Ambon State Polytechnic Civil Engineering Department. The Department of Civil Engineering Ambon State Polytechnic is one of the education that leads to Vokasih education, education that prepares human resources that are ready to use in the world work contest. The method used in this study is multiple regression analysis. This analysis is used to find out how much the independent variable (7P marketing mix strategy) is dependent on the dependent variable (Decision of service users to choose Ambon State Polytechnic Civil Engineering Department). The regression general equation used is as follows Y = α + ∑bnXn + e. The results of the calculation of independent variable relations and the dependent variable influence each other shows positivity. Y = 2,442 + (0,126) x1 + (- 0,009) X2 + (0,39) X3 + (0,131) x4 + (0,031) 5 + (0,037) x6 + (0,054) X7. Adjustd R squar value of 0.071 or 71% as an independent variable influences the dependent variable and the remaining residual value of 29% is influenced by other variables not included in the study. the overall value of F count is 2.448 and a significant value of 0.022. the result of the F table value is 2.10, then F count 2.448> 2.10 then Ho is rejected. Keywords: JTS Product Marketing, Service User Decision, Civil Engineering Department